A reflexive collaborative workshop on agroecology narratives and researchers’ postures - Richelle Lola; Brauman Alain; Romagny Bruno; Venot Jean-Philippe; Masse Dominique; Cournac Laurent; Leonard Éric; Imache Amar; Rizzo Davide (Natures Sciences Sociétés, 2024)
Agroecology has multiple interpretations and goals, driven by social movements, political contexts, and scientific needs. Agroecological transition processes generate tensions between social movements and institutionalisation processes. Researchers are thus caught between two potentially contradictory tasks: (i) advising policy-makers and (ii) supporting farmers and stakeholders in their endogenous trajectories. Here, we review a reflexive workshop that explored how agroecology narratives challenge researchers when supporting implementation of transdisciplinary collaborations. We highlight the need to create new researcher profiles, including facilitators in long-term partnerships, establish clear expectations, and develop ‘third spaces’ for collaboration. Qualitative research assessment and new epistemological approaches are crucial for sustainable science that bridges the gap between knowledge and local realities in agroecological transitions.